Periodic study on the structural and electronic properties of bulk, oxidized and reduced SnO2(110) surfaces and the interaction with O-2 - Sensato, F. R.; Custodio, R.; Calatayud, M.; Beltran, A.; Andres, J.; Sambrano, JR; Longo, Elson [UNESP] (Elsevier B.V., 2002)
The structural and electronic properties of bulk and both oxidized and reduced SnO2(110) surfaces as well as the adsorption process of O-2 on the reduced surface have been investigated by periodic DFT calculations at B3LYP level. The lattice parameters, charge distribution, density of states and band structure are reported for the bulk and surfaces. Surface relaxation effects have been explicitly taken into account by optimizing slab models of nine and seven atomic layers representing the oxidized and reduced surfaces, respectively. The conductivity behavior of the reduced SnO2(110) surface is explained by a distribution of the electrons in the electronic states in the band gap induced by oxygen vacancies. Three types of adsorption approaches of O-2 on the four-fold tin at the reduced SuO(2)(110) surface have been considered. The most exothermic channel corresponds to the adsorption of O-2 parallel to the surface and to the four-fold tin row, and it is believed to be associated with the formation of a peroxo O-2(2-) species. The chemisorption of O-2 on reduced SnO2(110) surface causes a significant depopulation of states along the band gap and it is shown to trap the electrons in the chemisorbed complex producing an electron-depleted space-charge layer in the inner surface region of the material in agreement with some experimental evidences. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: ab initio quantum chemical method and calculations; density functional calculations; models of surface chemical reactions; chemisorption; surface electronic phenomena (work function, surface potential, surface states. etc.); oxygen; tin oxides; semiconducting surfaces